Effect of glucagon-like peptide-1 (GLP-1) agonists on the example of semaglutide on the cardiovascular system and their role in the treatment of obesity. - Pondel, Kamil; Kawałko, Kinga; Bielewicz, Krzysztof; Chmura, Anna; Karaś, Anna (Journal of Education, Health and Sport, 2022)
Obesity nowadays affects an increasing number of people. We can talk about it when the patient’s BMI is ≥ 30.0 kg/m² (BMI 25.0-29.9 kg/m² - overweight). While obesity in itself may not be a problem for people suffering from it, its complications can be global and sometimes pose a serious threat to health or even life. Its main complications in the cardiovascular system include: hypercholesterolaemia, arterial hypertension, left ventricular hypertrophy, early atherosclerotic changes, heart and cerebral infarction. Treatment of obesity is based mainly on changing the patient’s lifestyle - diet and physical activity, which can sometimes be problematic and difficult to apply. However, there is a new group of hypoglycaemic drugs - glucagon-like peptide-1 (GLP-1) agonists, which can make obesity treatment easier. These drugs use the incretin effect in the body to increase insulin secretion in response to a meal containing carbohydrates and prevent postprandial hyperglycemia. In this article, we will analyze the latest studies on the effects of GLP-1 receptor agonists, using semaglutide as an example, on the cardiovascular system and on weight loss in patients.